Parametric Investigations on Laminated Composite Sandwich Plates with Honeycomb Core - Hozan Abdul-Jabbar Othman; Shiren Othman Muhammad (QALAAI ZANIST JOURNAL, 2024)
In this study, an analytical solution of multi layered laminated composite laminate plate is presented of a new form of composite sandwich panels in two different styles; Kevlar fibers bonded with honeycomb core in mid plane, and glass fibers bonded with honeycomb core in mid plane. Classical laminated plate theory has been used for modeling the sandwich plate, Ritz method has been used for calculating the plate’s maximum bending deflections. The results have been validated by Finite Element analysis with a good. The parametric investigations include, change in material types of lamina, different layer thicknesses, and several geometric cell shapes of honeycomb core laminated has been examined. The results proved that the Convex cell honeycomb core plays a great role in absorbing the force energy as a result it reduced the plate deflection by 8% better than semi-entrant and re-entrant, and Kevlar-49 is the best among other types of Kevlar. S2-glass fiber -Sandwich plates have reduced the plate’s overall deflections by 14.73% compared to Kevlar-29 -Sandwich plates.